Digital Health Intervention of Healthy Indonesia Program with Family Approach: Does it Work? - Prasiska, Danik Iga; Yaqin, Moch Jazil Ainul (Universitas Airlangga, 2023)
Background: The digital age holds out the promise of innovative technology. Along with the development of technology, healthcare management has been changing. Indonesia was implementing The Healthy Indonesia Program with a Family Approach (PISPK) that aimed at increasing access of families and their members to comprehensive health services, promotive, preventive, curative, and basic rehabilitative. Every household data related to 12 health indicators was digitally recorded and analyzed on a specific website to provide a database for determining suitable health and empowerment programs according to health problems experienced by the community. Objectives: This study aimed to assess the performance of The Healthy Indonesia Program with a Family Approach website in East Java Province, Indonesia. Method: The study design is cross-sectional with a descriptive exploratory study. Data was collected through an online survey utilizing Google Forms service and analyzed descriptively with a thematic content approach. Result: Respondents of this research involving 232 health workers from community health centers in East Java Province that running Healthy Indonesia with a Family Approach. This research result found that the PIS-PK website met the criteria of a digital health monitoring tool recommended by WHO with the score of Functionality (70.54%), Stability (62.89%), Fidelity (58.17%), Quality (73.81%), Implementation (77.41%), and Judgement (67.92%). Conclusion: Healthy Indonesia with Family Approach Website was beneficiary to be used as the baseline in designing and developing a community empowerment program targeting specific indicators at the community health center level. However, several issues were noticed including, stability, fidelity, privacy, and data governance that should immediately take into account to improve the website's performance.